Recusal : analysis of case law under 28 U.S.C. [sections] 455 & 144 - Hirsch, Alan, 1959-; Loveland, Genevra Kay (Federal Judicial Center, 2002)
"This monograph offers a synthesis and analysis of the case law under 28 U.S.C. [sections] 455 and 144 to assist judges in ruling on recusal"--Page v.